Dominating sublittoral fish species in a west Norwegian fjord and their trophic links to cod (Gadus morhua L.) - Salvanes, Anne Gro Vea; Nordeide, Jarle Tryti (The University of Bergen, 1993)
The fish fauna in the sublittoral habitat of Masfjorden, western Norway, has been studied in order to reveal survival and growth prospects of released juvenile cod in a large-scale stock enhancement experiment. Seasonal changes in abundance of dominating fish species and in the diet of potential competitors and predators to juvenile cod were emphasized. A total of 44 species from 17 families of Teleostei and 4 families of Chondrichthyes were recorded at 5-20 m depth of the sublittoral of Masfjorden. Gadids were dominating (50.2 % by numbers, 10 species) and saithe (Pollachius virens), pollack (P. pollachius), poor-cod (Trisopterus minutus) and cod (Gadus morhua) were most numerous. Labrids form a second dominating family (44.7 % by numbers, 5 species) of which Centrolabrus exoletus, Ctenolabrus rupestris, Labrus bimaculatus and L. bergylta were the most abundant. Pollack and saithe had highest abundance during summer and autumn. The labrids and poor-cod had maximum abundance in summer. All labrids, pollack and saithe showed minimum abundance in winter while poor-cod had lowest abundance in spring and highest in summer. Dietary studies showed that gobies were one of the major preys for small individuals of cod, pollack, saithe and poor-cod in the summer and autumn. Gadids and labrids were important prey for large cod and pollack.